PENGARUH KEMAMPUAN KERJA, MOTIVASI DAN KEDISIPLINAN TERHADAP KINERJA PARAMEDIS DI RUMAH SAKIT UMUM DAERAH LAMADDUKKELLENG SENGKANG - Andi Tenri Olle (STIE AMKOP, 2020)
The data collection methods in this study are questionnaire, interviews and documentation. Methods of data analysis using a descriptive method and quantitative method are the analysis of multiple linear regression used to measure the influence of ability, motivation and discipline of paramedic performance in the District general Hospital Lamaddukkelleng Sengkang consisting of ability, work motivation, discipline and paramedic performance. Based on the free variable F tests (ability, work motivation, discipline) together have a positive and significant influence on the bound variables (paramedic performance). Through the testing of Koefesien correlation (R) obtained that the level of correlation or the relationship between ability, work motivation and discipline of paramedic performance is a high relationship of 87.9%. And discipline is the most dominant factor in influencing the paramedic performance of the general Hospital of Lamaddukkelleng Sengkang District. Keywords: work ability, work motivation, discipline and paramedic performance